Rancang Bangun Alat Pemeriksa Run Out Roda Gigi menurut Standar ISO 1328 - Iwan Gunawan; Antonius Adi Soetopo; Rahmat Romadhona Prayoga (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2019)
One of the parameters is the reference to the quality of the gear that is run out. Run out is the change in the location of the current element rotates against a fixed point on the axis of reference. The method used to check for errors swivel gear that is by turning the gears are checked with the master gear. Checker tool run out of gears using stepper motors as gear and readings players run out using LVDT sensors. Mechanical construction specifications that is thedistance between spindle capacity maximum 170 mm. Maximum run out that can be read by the LVDT sensor is 3.50 mm. The operating system uses an interface program that can be adapted to the gear to be checked. Inspection run out gear carried on a pair of straight gears are split into two parts with module 2, number of teeth 34. The examination was conductedat four different gear positions, tolerance RCE (radial composite error) allowed for automotive applications (ISO grade 8) is0.09 mm, where the measurement results obtained from the smallest RCE at position 3 (1A on z-1 and 1B on the z -19) at 0.10 mm so we can say that the measured gear can not be used for automotive applications because the measured RCE exceed permissible limits.